Memperkuat Legalitas Usaha Kecil: Pendampingan Pembuatan Nomor Induk Berusaha Melalui Sistem Online Single Submission - Purwanto, Purwanto; Khaulah, Qonita (At Taawun Bangun Bangsa, 2025)
This community engagement activity aims to Strengthen Small Business Legality by providing assistance in obtaining the Business Identification Number (NIB) through the Online Single Submission (OSS) system. The core problem addressed is the significant implementation gap between the national digital licensing policy and the ground reality: low digital literacy and a minimal perception of business legality among Small Business actors in rural areas like Dusun Marongan, Sukomakmur Village. Operating without official licenses, these businesses are constrained from accessing government empowerment programs and formal capital. The method employed was Asset-Based Community Development (ABCD), strategically chosen to overcome the human factor challenges by focusing on activating the partners' intrinsic assets, particularly their strong aspiration for growth (dream). The core intervention was implemented intensively through hands-on, one-on-one technical assistance during the Destiny stage, serving as an effective novelty. The results successfully achieved were twofold: (1) the successful issuance of NIBs for the assisted Small Business partners, granting them formal legal legitimacy; and (2) increased digital confidence and technical skills among partners to utilize the OSS system independently. The conclusion is that the community-based assistance model (ABCD) offers a practical and crucial solution to overcome the digital implementation gap, directly fostering legal and sustainable small businesses.